Bismarck's Health Insurance and the Mortality Decline - Stefan Bauernschuster; Anastasia Driva; Erik Hornung (Center for Economic Studies and ifo Institute (CESifo), 2017)
We investigate the impact on mortality of the world's first compulsory health insurance, established by Otto von Bismarck, Chancellor of the German Empire, in 1884. Employing a multi-layered empirical setup, we draw on international comparisons and difference-in-differences strategies using Prussian administrative panel data to exploit differences in eligibility for insurance across occupations. All approaches yield a consistent pattern suggesting that Bismarck's Health Insurance generated a significant mortality reduction. The results are largely driven by a decline of deaths from infectious diseases. We present prima facie evidence that diffusion of new hygiene knowledge through physicians was an important channel.
Keywords: I13; I18; N33; J11; 330; health insurance; mortality; demographic transition; Prussia